The New Year brings some changes - Editorial (Blackwell Synergy, 2001)
The journal continues to move toward becoming a truly global voice for the rich variety of epidemiological, behavioral, and heath service-related research that is taking place in all parts of the world. Our theme here is that we can all learn something from each other.